Chaihu Guizhi Ganjiang Decoction Ameliorates Pancreatic Fibrosis via JNK/mTOR Signaling Pathway - Cui, Lihua; Li, Caixia; Shang, Ye; Li, Dihua; Zhuo, Yuzhen; Yang, Lei; Cui, Naiqiang; Li, Yuhong; Zhang, Shukun (Frontiers in Pharmacology, 2021)
Pancreatic fibrosis is a pathological characteristic of chronic pancreatitis (CP) and pancreatic cancer. Chaihu Guizhi Ganjiang Decoction (CGGD) is a traditional Chinese medicine, which is widely used in the clinical treatment of digestive diseases. However, the potential anti-fibrosis mechanism of CGGD in treating CP remains unclear. Here, we conducted a series of experiments to examine the effect of CGGD on the CP rat model and primary isolated pancreatic stellate cells (PSCs). The results revealed that CGGD attenuated pancreatic damage, decreased collagen deposition, and inhibited PSC activation in the pancreas of CP rats. However, compared with the CP group, CGGD had no effect on body weight and serum amylase and lipase. In addition, CGGD suppressed autophagy by downregulating Atg5, Beclin-1, and LC3B and facilitated phosphorylation of mTOR and JNK in pancreatic tissues and PSCs. Moreover, the CGGD-containing serum also decreased LC3B or collagen I expression after rapamycin (mTOR inhibitor) or SP600125 (JNK inhibitor) treatment in PSCs. In conclusion, CGGD attenuated pancreatic fibrosis and PSC activation, possibly by suppressing autophagy of PSCs through the JNK/mTOR signaling pathway.